Granting economic real estate in light of low 23-17 and its related decrees - Chabani, Nada; Laouamri, Walid (Journal of Human Sciences, 2025)
Algerian state, aiming to support investors in implementing their projects by allocating a substantial portion of its private national properties for this purpose. The provision of economic real estate is integral to the strategy of revitalizing the national economy and reducing dependence on oil. A law was issued in Issue No. 73 of the official journal, specifying the conditions and methods for granting economic real estate belonging to the state’s private property and aimed at completing investment projects. This law and its accompanying decrees are meant to complement the new investment law. Although the latter offers numerous tax, financial, and fiscal benefits for both foreign and local investors, its success depends on being accompanied by a set of reforms that improve the business in Algeria, especially through new legislative measures affecting various sectors to advance the national economy.